Evaluation and comparison of three-dimensional finite element analysis of stress distribution in immediately placed and loaded conventional and customized three-dimensional printed dental implants - Priya Saini; Vishakha Grover; Shaveta Sood; Ashish Jain; Parveen Kalra (Journal of Indian Society of Periodontology, 2023)
Aim: The aim of this study was to evaluate and compare the stress distribution patterns in immediately placed and loaded conventional and customized three-dimensional (3D) printed dental implants by 3D finite element analysis. Materials and Methods: Twelve 3D finite element models [Group A-3 models; Group B-9 models] with 72 test conditions which were modeled and compared from customized 3D printed dental implants [Group A] and 3 commercially available implant systems [Group B] (Straumann, Ankylos, and Astratech) using “SolidWorks”. All models were embedded in extraction socket models of the maxillary central incisor (CI) and Canine (C), Mandibular 1st Premolar. An occlusal loading by axial and nonaxial force of 100 N and 150 N at 30°C and 45°C was applied on the abutment using the “ANSYS” Suite. Customized 3D printed dental implant (Group A) for maxilla (Max.) CI, Max. C, and mandibular 1st premolar (PM) socket model was compared with three commercial available dental implant systems (Group B) for Max. CI, Max. C, and mandible (Mand.) 1st PM socket model to understand the stress distribution patterns. Results: With increasing oblique loads, von Mises stresses were reduced for the customized group as compared to conventional implants. Increased axial loads caused proportionate increase in the stresses for both groups, yet remained under the physiologic limits in all test conditions. Higher stresses were observed in cortical bone than in cancellous bone at bone–implant contact in general. Marked reduction in von Mises stress was observed at the boundary between compact and cancellous bone. Customized 3D printed implants performed better for oblique loads and comparable for axial load stress distribution in comparison to conventional implant systems in Max. CI and C, Mand. 1st PM. Conclusion: Thus, customized 3D printed implants appear a promising alternative for immediately placed immediately loaded protocols, with additional benefits in specific clinical situations.